EDITORAL - Kostrzewski, Andrzej; Stryjakiewicz, Tadeusz (Quaestiones Geographicae, 2019)
This volume of Quaestiones Geographicae is dedicated to the 100th anniversary of the establishment of the Poznań geographical centre. The tradition of geographical research is much longer, but it was not until Poland regained independence in 1918 and the University of Poznań was founded in 1919 that its institutional basis was created. Geography has existed at the University of Poznań since its very beginning (with a break during World War II). The founder of the Institute of Geography was Professor Stanisław Pawłowski, later the rector of the University of Poznań, secretary general of the 14th International Geographic Congress in Warsaw (1934) and Vice-President of the International Geographical Union (from 1938), murdered by German occupiers in 1940.